A Model for Implementing Medical Student Career Development Courses - Anita Navarro (Association of American Medical Colleges, 2010)
Abstract Introduction Medical students make career decisions with life-long implications during school. Careful decisions about specialty decisions are paramount to physician satisfaction. Further, the career decisions students make are increasingly important as the number of residency slots remain stagnant against the rising number of medical school graduates. This module contains materials for a required career course and an elective that are both geared for M2 students. The required course offers basic information about The Match, while the elective provides information on a personalized approach to specialty choice. Methods This resource provides facilitator course guides for both the required course and elective, as well as lesson plans for each of sessions of the courses. A student syllabus is also provided for each course. Results Taught since 2004, the elective grew in popularity until it became prudent to offer the content to all second-year students. Thus, all of our 200 second-year students are required to participate in the fall course. The spring course has always been an elective and enrollment has stabilized at about 12-20 students. The courses are well rated by students and enrollment in the elective has been consistent. Discussion Choosing a specialty can be a difficult decision, and several U.S. medical schools have recently begun to support this process through curriculum strategies. This module offers one way to offer medical student career development with two courses. A medical school could attempt either a second-year student elective or a required course or both as presented here.